Statement by The Managing Director on the Work Program of The Executive Board. (Policy Papers; Policy Paper ;, 2019)
This Work Program translates the strategic directions and policy priorities laid out in the Spring 2019 Global Policy Agenda and the International Monetary and Financial Committee Communique into an Executive Board agenda for the next twelve months. Its main policy priorities and related deliverables are as follows: -- Support domestic policies to enhance resilience and inclusion: -- Upgrade global cooperation to level the playing field and address other shared challenges -- Adapt the Fund's toolkits to lead and support change: -- Continue to modernize the Fund to deliver for the future:.